On fuzzy interior Γ-hyperideals of Γ-semihypergroups - Ersoy B.A.; Saricaoglu Y.; Yenigun M.; Davvaz B. (Utilitas Mathematica, 2012)
Algebraic hyperstructures represent a natural extension of classical algebraic structures. One of the classes of algebraic hyperstructures is the class of Γ-semihypergroups. In this paper, we investigate the notion of fuzzy interior Γ-hyperideal of a Γ-semihypergroup and investigate some of their properties.